ADVANCED CLAY-BASED GEOPOLYMER CEMENTS: STRUCTURAL BEHAVIOR, MATERIAL PROPERTIES, PARAMETRIC INFLUENCE, AND EMERGING APPLICATIONS - Ameer Hamza; Saleemullah; Nasir Rafique; Yasir Ansari; Basit Ahmad; Md. Refat Ferdous (Spectrum of Engineering Sciences, 2025)
The global construction industry is undergoing a transformative shift toward sustainable and low-carbon alternatives to traditional Portland cement. Among emerging materials, clay-based geopolymer cements have gained significant attention due to their eco-friendly synthesis, utilization of naturally abundant aluminosilicate clays, and exceptional mechanical and durability performance. This study provides a comprehensive investigation into the structural characteristics, physico-chemical properties, and influential synthesis parameters of clay-based geopolymer cements. Emphasis is placed on the reactivity of various natural clays such as kaolinite, montmorillonite, and halloysite under alkali activation, along with their phase transformations, microstructural evolution, and resulting geopolymer gel formation. Key parameters, including the Si/Al ratio, curing temperature, activator concentration, type of alkaline solution, and liquid-to-solid ratio, are critically analyzed for their impact on setting time, compressive strength, porosity, and thermal stability. The influence of calcination temperature and pre-treatment methods is also examined, particularly in enhancing the amorphous phase content and facilitating dissolution kinetics. Analytical techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA) are employed to characterize the mineralogical, morphological, and thermal behavior of geopolymer matrices. Furthermore, this paper evaluates the long-term performance of clay-based geopolymers in aggressive environments, including acidic and sulfate-rich conditions, highlighting their superior resistance compared to conventional cements. In addition to their structural utility, the multifunctionality of these materials is explored through applications in thermal insulation, fire resistance, carbon sequestration, and hazardous waste immobilization. By integrating original experimental findings with an extensive review of current literature, this study advances the understanding of clay-geopolymer chemistry and presents a pathway toward scalable, circular-economy-driven, and low-carbon construction materials for a sustainable future. The outcomes of this research are anticipated to significantly influence material selection in eco-construction, infrastructure resilience, and green architecture.